FACTORS INFLUENCING UNDER-REPORTING OF FINANCIAL PERFORMANCE AMONG STUDENT LUBS AND ASSOCIATIONS - Mohd Syazwan Karim; Khairiah Ahmad; Nur Farahah Mohd Pauzi; Azlan Md Thani; Adriana Shamsudin; Nurfarahin Roslan (International Journal of Accounting, Finance and Business, 2022)
This paper aims at understanding factors that contribute to under-reporting of financial performance among student clubs and associations. Accounting information is not important for business only, but it is also essential for clubs and associations to plan and manage their financial matters more effectively. However, most student clubs and associations do not keep a proper book of accounts since there is no legal obligation to do so. Another reason is because they perceive accounting is a very difficult process due to the lack of exposure in providing accounting records particularly for non-accounting students. Using qualitative research design, semi-structured interviews were conducted with 13 students who were the representatives of 13 different clubs and associations from a tertiary institution in Melaka, Malaysia. Results show lack of accounting knowledge, inadequate training and poor source document keeping are the key factors influencing under-reporting of financial performance among these student clubs and associations. Investigating the issues that contribute to under reporting of financial performance by the clubs and associations would be useful for the university Student Affairs Division in designing appropriate training to improve the club treasurers’ financial reporting.